Digital Transformation of Student Assignment Management through a Mobile-Friendly E-Learning System Integrated with WhatsApp Gateway and Google Drive - Syahrul Anwar; Abdul Robi Padri; Ade Bani Riyan; Eko Siswo Adi Sahputra (Syntax Literate, 2026)
Objective: To develop a mobile-friendly e-learning system for managing student assignments that integrates with a WhatsApp Gateway and Google Drive, aiming to translate digital transformation in higher education into simple, rapid, and integrated assignment management processes. Methods: This study employs a Research and Development (R&D) approach using the ADDIE model, which includes needs analysis, architectural design, prototype development, limited implementation, and evaluation of usability and functionality. The proposed system features assignment creation, automatic WhatsApp reminders, Google Drive file integration, submission status tracking, and mobile-first dashboards. The evaluation is conducted through expert validation, black-box testing, System Usability Scale (SUS) measurement, and Likert-based user perception questionnaires. Results: The implementation of the system is expected to yield improved on-time assignment submissions, a reduction in late submissions, a more efficient workflow for lecturers, and the establishment of an economical yet reliable small-scale personal Learning Management System (LMS) model. Conclusion: This research provides significant practical contributions for educational institutions seeking a lightweight, compliant, and readily adoptable digital assignment management system that enhances learning flexibility and academic engagement.